MODELO DE DISPERSION DE CONTAMINANTES EN AGUAS RASAS - Yzocupe, Víctor A. (2005)
The study presents a two dimensional model of dispersion of pollutants built on the basis of a hydrodynamic model developed in a previous work. The coupled model is based on the numerical approach of the two dimensional shallow water flow equations and of the dispersion of substances. Thesc equations are of the continuity of the fluid body, of movement in directions X and Y, and conservation of the concentration of a diluted substance. The dependent variables are the average speeds U and V in directions X and Y respectively, the level of water 1J respect to the mean sea leve!and the concentration C of the diluted substance. The numerical approach is based on the Fischer's explicit finite difference scheme. The model has suitable initial and boundary conditions. The model has been tested under several theoretical experiments, after these tests, it was applied to the Paracas Bay. First, we did the simulatíon ofthe wínd dríven flow connected with the process of dispersion of pollutants for one single submarine outfall with constant flow for uniform wind fields from the south and from the west. After this, it was simulated a real wind field with space variation ofhis magnítude and direction, for the case of one single outfall and also for the seven main submarine outfalls ofthe bay. This application allows us to reproduce the dispersion ofpollutants pattems as answer ofthe geography'and the wind system ofthe region.